The fossils of castor fiber from the middle Pleistocene site of Gruta da Aroeira (Portugal) and human-beaver interaction - Cuenca-Bescós, Gloria (2021)
Here we analyze the fossil remains of Castor fiber from the Middle Pleistocene site of Gruta da Aroeira, in the Almonda karst system, Tagus basin (Torres Novas, Portugal) and discuss the archaeological implications of the presence of beavers in the region. The Almonda karst system has been the backdrop for human evolution in Portugal, because there are different localities, of different ages, from the Middle Pleistocene to the Holocene, with fossil remains of hominins as well as faunal and archaeological remains. Beaver fossils have been found in the archaeological deposits of at least three cavities of the karst system: the Gruta da Aroeira, the Gruta da Oliveira and the Galeria da Cisterna. Here, for the first time, we describe the fossils of Castor fiber from Gruta da Aroeira. The beavers from Aroeira are remarkable because they are the westernmost fossil record of Castor fiber in Europe dated to Marine Isotope Stage (MIS) 11, around 420 ka. The aim of the present article is twofold, firstly to study the fossils of beavers from the Aroeira locality, and secondly to discuss the palaeoecological and palaeoenvironmental implications of the presence of this rodent in the Almonda karst sites. This allows us to discuss the hominin-beaver interactions.